'Taprose Temanku' Sebagai Strategi Komunikasi Pemerintahan dan Pelayanan Publik Kabupaten Tuban - Isnaini Kun Faizah; Tony S. Soekrani; Redi Panuju (Fakultas Ilmu Komunikasi UKWMS, 2021)
This study discusses government communication using applications as public services and the Tuban government communication strategy. Tuban Government has the TapRose Temanku application which is a place for the community to submit criticisms, suggestions and questions. The focus of this research is how the strategy of the Tuban government and what kind of public services the Tuban government has done through the TapRose Temanku Application. This qualitative research uses data collection techniques, interviews, observation, and documentation. The results of this research are the TapRose Temanku application is a public service conducted by the Tuban Government and is a government communication strategy. The TapRose application, my friend, attracts the public's interest because it is packaged in a simple and easy to understand way for all ages and easily accessed.